1997
DOI: 10.1086/310671
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamical Models of Superluminal Sources

Abstract: We present numerical simulations of the generation, evolution, and radio emission of superluminal components in relativistic jets. We perform the fluid dynamical calculations using a relativistic time-dependent code based on a high-resolution shock-capturing scheme, and then we calculate the radio emission by integrating the transfer equations for synchrotron radiation. These simulations show that a temporary increase in the flow velocity at the base of the jet produces a moving perturbation that contains both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
233
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(248 citation statements)
references
References 26 publications
15
233
0
Order By: Relevance
“…In contrast to the expected flux density evolution of a traveling shock, we observe that C1, C3, and C4 show some local increase in their flux densities while they propagate downstream around r 0.1−0.2 mas. This could be explained in terms of the interaction of this shock with a standing recollimation shock (e.g., Gómez et al 1997;Mimica et al 2009 appear if the jet and the ambient medium are not in pressure equilibrium at the nozzle. Our observations do not allow us to resolve any change in the jet direction at this position, and neither the Doppler factor (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the expected flux density evolution of a traveling shock, we observe that C1, C3, and C4 show some local increase in their flux densities while they propagate downstream around r 0.1−0.2 mas. This could be explained in terms of the interaction of this shock with a standing recollimation shock (e.g., Gómez et al 1997;Mimica et al 2009 appear if the jet and the ambient medium are not in pressure equilibrium at the nozzle. Our observations do not allow us to resolve any change in the jet direction at this position, and neither the Doppler factor (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of their flux densities show that Q1 becomes unusually bright (2.1 Jy) on 2013 December 16, followed by a similar increase in flux density of Q2 (1.1 Jy) on 2014 January 19. This could be associated with the passing of a new component, M1, through the standing features, leading to a brief increase in their flux densities (e.g., Gómez et al 1997). Component M1 is identified in the last two epochs as a weak knot beyond 0.5 mas from the core.…”
Section: Evidence For Emission Upstream Of the Corementioning
confidence: 99%
“…The initial set-up follows Gómez et al (1997) and Mizuno et al (2015), in which a preexisting over-pressured flow is established across the simulation domain. We choose a restmass density ratio between the jet and ambient medium of r (e.g., Gómez et al 1995Gómez et al , 1997Mimica et al 2009). We assume that the jet is initially uniformly over-pressured with p p 1.5…”
Section: Pattern Of Recollimation Shocksmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the onset of turbulence (or return to laminar flow) behind a shock front might cause the magnetic field geometry to change within a short distance of the shock front. In addition, numerical hydrodynamical simulations (Gomez et al 1997) have shown that both propagating and standing shocks can be significantly thinner than the width of the jet. For favorable geometries, it is possible for the inferred brightness temperature to be lowered by two powers of the ratio of the line-of-sight thickness of the emission region to the transverse dimension of the jet.…”
Section: Rapid Variability and The Brightness Temperature Limitmentioning
confidence: 99%